The Effect of Adding Soil Amendments on Some Soil Physical Properties and the Growth of Sunflower Crop in Clay Soil - Talal J. Al khanfous; Nihad Sh. Al-Wally; Sadiq J. Muhsin (University of Thi-Qar Journal of agricultural research, 2023)
The experiment was conducted in clay soil at the Agricultural Research Station affiliated with the College of Agriculture, University of Basra, during the spring of 2021. Research aimed to study the effect of soil amendments on soil physical properties such as (bulk density, total porosity, and electrical conductivity) and some growth and yield of sunflowers such as (plant height and dry weight). The soil amendments used in the experiment were cattle manure and synthetic polymer. The amendments were added to the surface layer of the soil at a depth of 15 cm, using individual and mixed application treatments with six levels of addition (Cont, P4, O4, P3O1, O3P1, and P2O2). The field was divided into plots measuring 2.5 m in length and 1.5 m in width, and then the plots were planted with sunflower seeds. The results showed that all the amendment treatments outperformed the treatment without amendments, improving the soil’s physical properties by reducing bulk density, increasing total porosity, and decreasing electrical conductivity. Additionally, the amendment treatments showed improvement in growth and yield characteristics, indicated by increased plant height and dry weight of the plants.